Analysis of the Development of Hong Kong Modernist Literature from The Drunkard - Zhong, Chenyang (Transactions on Social Science, Education and Humanities Research, 2024)
The Drunkard is the first stream-of-consciousness novel in China. Liu Yichang used inner monologue, time montage, metaphor, metaphor and implication to describe the stream-of-consciousness of the drinkard and the inner world of the literati, which is full of contradictions caused by reality in Hong Kong society where money is first. Through the method-of-stream of consciousness, it expresses the drunkard's inner adherence to serious literary creation and compromise to reality. The pursuit of living with dignity and the pressure of reality have shaped the image of the struggling, contradictory drunkard, thus reflecting the twists and turns of the development of modernist literature in Hong Kong, as well as the downtrodden life and inner anguish of the creators of modernist literature, and a critique of Hong Kong's social realities.